Pengaruh Pemberian “Contrash Bathing” Terhadap Penurunan Spatisitas Otot Lengan Dan Tungkai Pada Anak Dengan Cerebral Palsy - Afrianti Wahyu Widiarti; Yuliana Ratmawati (Interest : Jurnal Ilmu Kesehatan, 2018)
Abstract: Muscle spasticity, Contrash bathing, Cerebral palsy, Ashworth Scale. CP or cerebral palsy is a condition brain damage in childhood where there is a motor limitations caused by static lesions, non-progressive brain. CP showed abnormalities in muscle tone, causing a disturbance in the form of uncontrolled muscle tension or spasticity so that children are not able to perform functional movements. The aim of this study was to determine the influence of granting contrash bathing or showering in contrast with the water cold temperature (18 degrees Celsius) and the water warm temperatures (38 degrees Celsius) alternately with the duration of a specified time so that the muscles will experience the relaxation or muscle relaxation in the hope of limbs in children can be moved easily. There is the effect of bathing contrash therapy to decrease muscle spasticity in children with cerebral palsy. This study is a quasiexperimental study with two group pre and post test design. The subjects were all patients with CP in Yogyakarta WKCP that meets the criteria of inclusion, exclusion and drop out. The study was conducted for 8 weeks. Data collected were analyzed using SPSS 16.0. The different test within groups measured with Wilcoxon test, and for between groups measured with Mann Whitney test. The significance level was set on 0,05. The Results is the contras bath can reduce spasticity muscles in your arms and legs to cerebral palsy (p = 0.011 and p = 0.025.